Simulation of left ventricle flow dynamics with dilated cardiomyopathy during the filling phase - Chan, B.T.; Ong, C.W.; Lim, N.; Abu Osman, Noor Azuan; Al Abed, A.; Lovell, N.H.; Dokos, S. (2012)
Dilated cardiomyopathy (DCM) is a common cardiac disease which leads to the deterioration in cardiac performance. A computational fluid dynamics (CFD) approach can be used to enhance our understanding of the disease, by providing us with a detailed map of the intraventricular flow and pressure distributions. In the present work, effect of ventricular size on the intraventricular flow dynamics and intraventricular pressure gradients (IVPGs) was studied using two different implementation methods, i.e. the geometry-prescribed and the fluid structure interaction (FSI) methods. Results showed that vortex strength and IVPGs are significantly reduced in a dilated heart, leading to an increased risk of thrombus formation and impaired ventricular filling. We suggest FSI method as the ultimate method in studying ventricular dysfunction as it provides additional cardiac disease prognostic factors and more realistic model implementation.